(3JGQjN GdSdWGf Sdje GdYKeGfi eY GdSdWGf bGfUhI GdZhQis - (3CMeO Hf Ydj Hf CMeO Hf RfHd GdQeGd , J HYO (B980 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd hGdUdGI hGdSdGe Ydi GdfHi hUMHg hGdBd s
(3BNQgG (B:s
(3Ke Jhdi HYOg Ydi HGTG GdWhGTi hcGf ef Cgd GdNjQ hGdOjf hGdUdGM aCbGe HgG Edi Cf eGJ hOaf HGdbQGaI HGdbQH ef JQHI GdbGVi HcGQ LeYge Gddg JYGdi QMeg hGSYI s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B180s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B409 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B27 s
Keywords: (3GdJGQjNs